PENGARUH KOMUNIKASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN KP. MAKASSAR JAKTIM - Fitri Rahmayani; Nuridin (Jurnal Manajemen Bisnis Krisnadwipayana, 2022)
Purpose To determine the effect of communication and motivation on employee performance of Kantor Kecamatan Kp. Makassar Jaktim. This research is included in the category of causal associative research using a quantitative approach. The respondent in this study were employees of Kantor Kecamatan Kp. Makassar Jaktim, Satgas Sumber Daya Air. The sampling technique of this study used non-probability saturated sampling. The research method using partially and simultaneous linear regression analysis. The results of the study indicate that simultaneous or partially, communication and motivation have a positive and significant effect on employee performance of Kantor Kecamatan Kp. Makassar Jaktim.